2009
DOI: 10.1542/peds.2008-1382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cell Phone Distraction on Pediatric Pedestrian Injury Risk

Abstract: Our results suggest that cell phones distract preadolescent children while crossing streets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 15 publications
4
76
1
1
Order By: Relevance
“…Given the inherently immersive and absorbing nature of ARGs, the dangers of playing Pokémon GO are likely to be similar to future ARGs. Research has shown that children engage in unsafe pedestrian behaviors when distracted by cell phones [36], and ARGs provide another enticing distraction that may put gamers at risk of injury and motor vehicle accidents, dangers that are largely preventable. While rates of injuries that result specifically from playing ARGs have not been studied, it is known that unintentional injuries are the leading cause of death among 5-44 year olds, which captures the majority of Pokémon GO players [37].…”
Section: Physical Safetymentioning
confidence: 99%
“…Given the inherently immersive and absorbing nature of ARGs, the dangers of playing Pokémon GO are likely to be similar to future ARGs. Research has shown that children engage in unsafe pedestrian behaviors when distracted by cell phones [36], and ARGs provide another enticing distraction that may put gamers at risk of injury and motor vehicle accidents, dangers that are largely preventable. While rates of injuries that result specifically from playing ARGs have not been studied, it is known that unintentional injuries are the leading cause of death among 5-44 year olds, which captures the majority of Pokémon GO players [37].…”
Section: Physical Safetymentioning
confidence: 99%
“…Research on children's pedestrian behaviours has steadily increased (e.g., Barton and Schwebel 2007b;Dunbar et al 2002;Rosenbloom et al 2008;Stavrinos et al 2009;Zeedyk et al 2002). However, relatively few studies have investigated the pedestrian behavior of adults when accompanying children (Morrengiello and Barton 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Active engagement in telephone conversation is known to have adverse consequences on cognition: Speaking on a telephone reduces driver accuracy (Strayer & Johnston, 2001) and has negative consequences for pedestrian safety (Stavrinos, Byington, & Schwebel, 2009). …”
mentioning
confidence: 99%